In-vitro Comparison of the Impact of Four Types of Resin Composite on the Repaired Bond Strength and Surface Roughness After Sandblasting - K khorgami; M Sadaghiani; N Nemati (Islamic Azad University, 2016)
Abstract Background and Aim: One of the major problems with resin composite restorations is the weakness of bonding between the new and aged composites. Since appropriate micromechanical retention is necessary for the repair of aged resin composite restorations, the level of surface roughness after sandblasting can be influential in this regard. Considering the diverse composition of available resin composites in the market, the present study was performed to compare the impact of four resin composite types: Micro-hybrid (Z250), Nano-fill (Z350XT), Nano-hybrid (Z250XT) and Silorane-base (p90) on the repaired bond strength and surface roughness after sandblasting. Methods and Materials: In this in-vitro experimental study, 44 resin composite discs with the diameter of 6mm and height of 2mm were divided to 4 groups of Micro-hybrid, Nano-fill, Nano-hybrid and Silorane-base and from 11 samples of each resin composite type, one sample was evaluated for surface roughness level before and after sandblasting with Atomic Force Microscope (AFM) and 10 samples were tested for shear bond strength in universal testing machine. Results:The findings indicated that Micro-hybrid resin composite had the highest shear bond strength (37.8±6.4 MPa) followed respectively by Nano-fill (30 ±3.8 MPa), Silorane-base (17.9±4 MPa) and Nano-hybrid composites (7.6±1.9 MPa). The differences between all groups were significant (p <0.000). Before sandblasting, Nano-hybrid type had the highest level of surface roughness (505 ±154nm) and the lowest value was related to Micro-hybrid resin composite (94±35nm)  (p<0.000). After sandblasting, Nano-fill (1997±288nm), Silorane-base, Micro-hybrid and Nano-hybrid composites (1284 ± 645nm) showed the highest increase in surface roughness, respectively (p<0.4). Conclusion: In the present study, sandblasting caused a significant increase in the surface roughness of the four studied resin composite types. Despite the lowest surface roughness of Micro-hybrid type, it showed the highest bond strength amongst other composites after sandblasting.